2016
DOI: 10.1515/macvetrev-2016-0078
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Analysis of Dried Goose Carcasses

Abstract: M icrobiological studies on chicken meat and carcasses are well documented, but very few studies exist on goose meat and carcasses. Therefore, in this study, dried goose carcass samples were collected from the local households in Kars/Turkey and microbiologically analyzed in terms of public health risks. The total mesophilic viable count was found to be 6.58 (mean log10 CFU g -1 ) (100%). The number of Enterobacteriaceae was 4.85 (92.8%). Coliform bacteria was counted at the numbers of 2.98 (67.8%), while it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Therefore, the count of Enterobacteriaceae is estimated to reach higher levels if these products are not stored under cold conditions. Furthermore, a high count of Enterobacteriaceae also indicates that hygienic conditions cannot be ensured in obtaining the carcass and/or product production ( Güven et al., 2004 , Kamber and Yaman, 2016 ). Kamber and Yaman (2016) also reported that the count of Enterobacteriaceae varied between 2.30 and 7.00 log cfu/g in 92.8% of dried goose carcass samples collected from the local households in Kars.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the count of Enterobacteriaceae is estimated to reach higher levels if these products are not stored under cold conditions. Furthermore, a high count of Enterobacteriaceae also indicates that hygienic conditions cannot be ensured in obtaining the carcass and/or product production ( Güven et al., 2004 , Kamber and Yaman, 2016 ). Kamber and Yaman (2016) also reported that the count of Enterobacteriaceae varied between 2.30 and 7.00 log cfu/g in 92.8% of dried goose carcass samples collected from the local households in Kars.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a high count of Enterobacteriaceae also indicates that hygienic conditions cannot be ensured in obtaining the carcass and/or product production ( Güven et al., 2004 , Kamber and Yaman, 2016 ). Kamber and Yaman (2016) also reported that the count of Enterobacteriaceae varied between 2.30 and 7.00 log cfu/g in 92.8% of dried goose carcass samples collected from the local households in Kars. Furthermore, the mean coliform group bacteria count was determined to be 2.98 ± 0.31 log cfu/g (minimum: 2.30, maximum: 6.41 log cfu/g) in 67.8% of the samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations